Building occupants’ knowledge on fire safety evacuation plan at shopping mall : evacuation pathway - Nabihah, Abdul Malik (2018)
Fire safety consideration give influence when designing a building. Tragic disaster such as fire in large public and residential buildings (cafes, trades, and building) usually results in tragic consequences in people and environment. Studying the level of awareness and knowledge about fire safety evacuation plan particularly at the shopping mall can prevent possibility of injury, fatality or loss of property. Data collection was done using three methods that are questionnaires, walkthrough inspection and interview. Data was analyze using descriptive statistics because no association or relationship that need to be studied. The mean from the Likert Scale was used to determine the level of awareness among building occupants. The level of awareness is moderate. Management of the shopping mall was found to be lack in fire safety knowledge. In conclusion, the level of awareness on fire safety evacuation plan can be improved by training and education, digital screen display, installation proper signage and also compounding action by the management of the shopping mall.